Penerapan Kaidah Bahasa Indonesia yang Baik serta Analisis Kesalahan Fonologi dan Morfologi - Athirah, Siti Athirah Permaisuri; Rahma Ashari Hamzah; M. Ashri Said (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The purpose of this study is to analyze the application of Indonesian language rules and analyze phonological and morphological errors. Indonesian as the official language of the country is able to unite various ethnicities and cultures spread throughout the country. Teaching Indonesian does not only focus on language rules, but also provides a solid foundation for students to develop their communication skills. The method in this study uses the library research method or can be called library research. This method is used by collecting data by analyzing or reading a book, journal, document analysis, other literature studies to analyze things that are relevant to the topic being discussed. This method is used because it is to explore theories about how to apply phonology and morphology and how to analyze errors that occur in phonology and morphology. In this library research, the author collects data and studies it gradually and analyzes theories in books, journals, and other literature studies.